3D Printing and CNC Fabrication with SketchUp - Cline, Lydia Sloan (McGraw-Hill's AccessEngineering., 2016)
Filled with illustrated, step-by-step examples, this hands-on guide teaches beginners how to use SketchUp to make a digital model and how to use a personal machine, service bureau, or community Maker Space to fabricate it.